The Role of TV Series in Leading People to Sports: An Analysis on Archery - Bilim, Adem; Zelyurt, Mert Kerem (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
Watching television is a free time activity that people prefer significantly. Studies have shown that television has certain effects on people. Archery is an important sport in Turkish society. In this study, it is aimed to examine the relation between people's orientation to archery and television series. Qualitative research method was applied in the study. Purposeful sampling method was used to determine the sample. The sample of the study covers the archers-themed series audience who has been receiving archery training in the Okçular Vakfı (Foundation) and İBB (The İstanbul Metropolitan Municipality) Spor İstanbul both of which are located in İstanbul. The sample consists of26 people between the ages of 9-17 and 18-65. Semi-structured interview was used as the data collection technique. The results were classified under; “Demographic characteristics of the participants”, “meeting archery and starting archery”, “meanings of archery, reasons for interest and orientation to archery”, “interest in archery-themed series”, “orientation to archery through series”, “heroes in the series and the identification effect”, “on archery future plans and expectations” titles. According to the results obtained; Archery themed series such as Tozkoparan and Diriliş: Ertuğrul enables the participants to meet archery. The series in question appeared to be watched by the participants with great interest. TV series such as “Tozkoparan” and “Diriliş: Ertuğrul” have a great influence on the orientation of a significant part of the participants to archery. Its directing effect to archery sport is low in some participants whereas it is significant in most participants. It is seen that the participants want to be archers like the characters in these series, they use the techniques they learn from the characters, they try to shoot arrows by watching television and exhibit such identification behaviors. In addition, the participants have been found to have plans to become a trainer, to be an athlete and to continue as a hobby. In the final analysis, the results we have obtained in our study reveal that TV series with themes related to Archery and other branches of sports such as “Tozkoparan” and “Diriliş: Ertuğrul” have the potential to encourage people of all ages to sports and have a stimulating potential. We think that increasing the number of television series covering themes related to developing sports branches that are not as mediatic as desired will be functional in increasing popularization and awareness levels of amateur and developing sports branches.